The Moderating Effect Of Information Asymmetry On The Relationship Between Accounting Conservatism And Earnings Quality - An Empirical Study On Companies Listed In Damascus Stock Exchange- - مالك حاتم اياد (Latakia University Journal - Economic and Legal Sciences Series, 2024)
Earning quality is considered one of the main basis that management seeks to achieve and maintain, specially in the cases of uncertainty and conflict that might companies suffer. To achieve that goal managements try to follow conservative Accounting polices that take into account all risks that might face their works. These polices is enhanced in case of information asymmetry that each part has and results from the separation between management and ownership. Based on that, this study aimed to determine the impact of accounting conservatism on earning quality, as well as the moderator impact of information asymmetry on the relationship between accounting conservatism and the earning quality. The data is collected using annual financial reports for companies listed in Damascus Stock Exchange. These reports are available on Damascus Stock Exchange website. Using a dataset of 18 listed companies covering the period 2013 to 2022 comprising a total of 180 observations, Panel Data analysis is employed, with the help of the application Eviews 10 and Microsoft Excel 2010. The study used time-sectional data Panel Data Balanced. The earnings quality variable was measured based on persistence of earnings, proximity to cash, and earnings management, while accounting conservatism was measured by dividing the market value of equity to the book value of equity, and information asymmetry was measured based on trading volume. The results showed that there is no effect of accounting conservatism on the earnings quality, as well as the absence of any moderating effect of the information asymmetry variable.